Akibat Hukum Putusan Gugatan Sederhana Tidak Dijalankan bagi Para Pihak - Naefi, Mohammad; Latifiani, Dian (Universitas Negeri Semarang, 2021)
Small Claim Court is the implementation of a case examination carried out in a simple procedure. With a court judgment being handed down in the trial process, it does not mean that the case is declared finished. It is necessary to carry out the implementation of the decision, namely execution if the losing party in the trial does not want to carry out the contents of the decision voluntarily. The problem in this study is what are the legal consequences for each party if the execution of the court jugdment in the default case through Small Claim Court in the Pengadilan Negeri Brebes is not carried out?. This research is an empirical research using a qualitative approach. Required a primary data and secondary data in an empirical legal research. To be able to obtain the necessary data, the author uses several ways, namely by conducting interviews, literature studies, reviewing documents. The results of the research that have been carried out explain that if there is no request for execution and the execution is not carried out, the legal consequences for the defendant as the debtor must still carry out the court jugdment by paying the remaining debt to the Plaintiff. In order to fulfill the debt, the defendant can independently sell the defendant's assets to pay off the remaining debt of the defendant to the plaintiff. While the legal consequences for the Plaintiff as the creditor, the Plaintiff still has the right to the debt to the Defendant as the debtor and the receivable must be paid immediately by the Defendant as the debtor. So the Plaintiff as the creditor continues to carry out parate executions based only on a power of attorney to sell the collateral, the Plaintiff can be declared to have committed an unlawful act.